x(3y-2)+5y=6
=>x(3y-2)+6y-4=y+2
x(3y-2)+2(3y-2)=y+2
(3y-2)(x+2)=y+2 => 3y-2 la uoc cua y+2=>y+2chia het cho 3y-2
=>3y+6 chia het cho 3y-2
Rổi tru di va lâp bang la xong
\Leftrightarrow x=[TEX]\frac{6-5y}{3y-2}[/TEX], chú ý rằng y∈Z⇒y≠23⇒3y−2≠0.
Suy ra [TEX]\frac{6-5y}{3y-2}[/TEX] ∈Z \Rightarrow (3y−2) ∣ (6−5y)\Rightarrow(3y−2 ) ∣ 3(6−5y)=18−15y.
Mặt khác (3y−2) ∣ 5(3y−2)=15y−10.
Do đó (3y−2) ∣ (18−15y+15y−10) = 8 \Rightarrow 3y−2∈{−1,1,2,−2,4,−4,8,−8}
\Rightarrow y∈{1,0,2,−2}.
Thay ngược lại để có (x,y)∈{(1,1),(−3,0),(−1,2)}.